Recurrence analysis of the mass movement activity at Stambach (Austria) based on radiocarbon dating - Unkel, Ingmar; Ehret, Dominik; Rohn, Joachim (Geomorphology, 2013)
The Stambach mass movement (Austria) is a large and deep-seated mass movement in the Austrian Alps. It consists of a complex and compound mass movement system. The latest major reactivation of the Stambach mass movement was initiated in 1982 by rock fall activity that triggered an earth flow, which transformed into a mud flow. Six sediment cores were taken along the entire earth flow body showing a complex mixture of rock fall blocks and earth flow material. Whenever the earth flow was active, numerous wooden remains were buried within the flow mass. Thirteen of these remains sampled from the sediment cores were radiocarbon dated. The results indicate that the first activation of the Stambach mass movement occurred at least around 9750-9900cal BP, followed by at least three further events during the Holocene, around 6310-5650, 2320-1880, and 1600-1180cal BP. Accumulation of toppled rock towers in the head area of the earth flow, followed by a sudden collapse and saturated, undrained loading of the earth flow body, is the main trigger for activating the earth flow. These long lasting preparatory processes make it difficult to determine certain recurrence intervals. However, our data show that the Stambach mass movement was (and most probably still can be) reactivated after more than 3000years of dormancy.
Gesehen am 19.02.2025
Online verfügbar: 4. März 2013